2017
DOI: 10.1111/1759-3441.12184
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Contribution of Circumstances that Reflect Inequality of Opportunities

Abstract: Until recently, researchers have typically followed an indirect approach to decomposing income inequality into its “fair” and “unfair” components, by examining income mobility. This study contributes to the existing literature by demonstrating the advantages of employing a direct approach, through measuring the contribution of various sources of inequality of opportunities. Based on recent Australian data, we estimate that at least 8 per cent of total income inequality before government transfers and taxes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…While these results are not directly comparable because of the different datasets and circumstance variables included in each paper (e.g. De Barros et al, 2009;Ferreira and Gignoux, 2011;Martinez et al, 2017), it still seems reasonable to claim that China has a serious inequality of opportunity problem, with gender playing a very significant role.…”
Section: Inequality Of Opportunity In China's Individual Labor Earningsmentioning
confidence: 90%
See 1 more Smart Citation
“…While these results are not directly comparable because of the different datasets and circumstance variables included in each paper (e.g. De Barros et al, 2009;Ferreira and Gignoux, 2011;Martinez et al, 2017), it still seems reasonable to claim that China has a serious inequality of opportunity problem, with gender playing a very significant role.…”
Section: Inequality Of Opportunity In China's Individual Labor Earningsmentioning
confidence: 90%
“…of individual labor earnings in Mexico, at 3−4 percent. In their analysis of individual income inequality in Australia between 2001 and 2013, Martinez et al (2017) similarly showed the relatively small contribution of gender to total income inequality of less than 6 percent (compared to more than 50 percent for father's occupation, the most important circumstance). These small contributions contrast starkly with the dominant role we find played by gender in the empirical analysis of China that follows.…”
Section: Analysis Of Individual Labor Earnings In Five Latinmentioning
confidence: 99%
“…De Barros et al (2009) find a similar share for gender in the inequality of individual labour earnings in Mexico, at 3-4 per cent. Martinez et al (2017) also use gender as a circumstance in their analysis of Australian individual income inequality between 2001 and 2013, revealing rising gender disparities over that period, but still a relatively small contribution of gender to overall income inequality, of less than 6 per cent (compared with more than 50 per cent for father's occupation-the most important circumstance). These small contributions contrast starkly with the dominant role we find for gender in the empirical analysis for China that follows.…”
Section: Inequality Of Opportunity Circumstances and Effort Backgroundmentioning
confidence: 99%
“…Checchi et al (2015) argued that differences of circumstances which people face at household level and institutions are key to the differences of their incomes. By using different personal as well as parental characteristics such as gender, country of birth, race and ethnicity as variables to reflect circumstances, and gross as well as net income as outcome variables, Martinez et al (2017) have found that circumstances are crucial to determine the differences of incomes among individuals.…”
Section: Literature Reviewmentioning
confidence: 99%